Education and Health Services in Kenya : Data for Results and Accountability - Martin, Gayle H.; Pimhidzai, Obert (World Bank, Washington, DC, 2013)
Although Kenya's vision 2030 highlights investment in human development, public spending on health and education in Africa has not guaranteed results. Closing the gap between promises, spending, and results depend on what service providers know and what they do: provider behavior is key. The Service Delivery Indicators (SDI) aim to provide critical information to improve accountability for health and education results. The survey was implemented by the Kenya Institute of Public Policy Research and Analysis (KIPPRA) and Kimetrica with quality assurance and oversight from the World Bank. The surveys provide a representative snapshot of the learning environment and key resources in both public and private schools, and the quality of health service delivery and the physical environment within which services are delivered in public and private (nonprofit) health facilities. Improvements in service quality in Kenya can be accelerated through focused investments on reforms to the incentive environments facing providers, and in the skills of providers to ensure that inputs and skills come together at the same time and at the same place. This will be critical to ensure that Kenya's gains in human development outcomes continue beyond 2015, bringing the country closer to achieving the promises set out in the vision 2030.